(untitled) (Semiárida, 2020)
Evaluation of a clonal population of Tetrachne dregei Nees. n. Depth and sowing method. The main limitation for the extensive cultivation of Tetrachne dregei Nees is the difficulty to obtain its establishment. The purpose of this work was to determine the appropriate sowing depth, and to compare sowing and compactation methods. In plastic trays with sterilized soil under controlled photo and thermoperiod, emergency curves were obtained for anthecium and caryopsis sowed at different depth. Results were analized by Tukey test and regression. It were compared five sowing methods, with a common distribution system. Emergence percentage was never smaller than 50% for anthecium and caryopsis sowed between O and 2 cm. deep. Ploughing and line compactation showed to be the best treatment to obtain tetracne establishment. Degree and type of weeds had an adverse effect on its establishment.